PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP SEMANGAT KERJA OPERATOR SEKOLAH DASAR NEGERI DI KECAMATAN TAPEN KABUPATEN BONDOWOSO - Djoko Suhartono; Sofia Nurhasanah (ACTON, 2017)
One of the benchmarks of a country's progress is Education. Currently, Indonesia is starting to improve its education quality which is marked by the establishment of School Operator (OPS). Methods of data collection is done by observation methods, interviews, and the spread of questionnaires (questionnaires). Data analysis technique used is Multiple Linear Regression Analysis. Based on the analysis, it can be concluded that the partial test of Leadership variable has positive and significant influence while the Compensation variable has negative and insignificant influence to the Working Spirit of Primary School Operator in Tapen Sub-district, Bondowoso District. while the simultaneous test (together), Leadership variable (X1) and Compensation (X2) have a positive and significant influence to the morale of Public Alementary School Operator in Tapen Sub-district, Bondowoso District.